Assessment of four calculation methods proposed by the EC for waste hazardous property HP 14 'Ecotoxic'. (February 2016) - Hennebert, Pierre; Humez, Nicolas; Conche, Isabelle; Bishop, Ian; Rebischung, Flore
Highlights: The hazard property HP 14 'Ecotoxic' (the most frequent) is discussed at EU level. Four calculation methods with 120 wastes are compared with the European List of Waste. Method 3 and 1 match well, but best matching (80%) is obtained with full M -factors. Useful pre-calculated element concentrations and tables of M -factors are proposed. Abstract: Legislation published in December 2014 revised both the List of Waste (LoW) and amended Appendix III of the revised Waste Framework Directive 2008/98/EC; the latter redefined hazardous properties HP 1 to HP 13 and HP 15 but left the assessment of HP 14 unchanged to allow time for the Directorate General of the Environment of the European Commission to complete a study that is examining the impacts of four different calculation methods for the assessment of HP 14. This paper is a contribution to the assessment of the four calculation methods. It also includes the results of a fifth calculation method; referred to as "Method 2 with extended M -factors". Two sets of data were utilised in the assessment; the first (Data Set #1) comprised analytical data for 32 different waste streams (16 hazardous (H), 9 non-hazardous (NH) and 7 mirror entries, as classified by the LoW) while the second data set (Data Set #2), supplied by the eco industries, comprised analytical data for 88 waste streams, all classified as hazardous (H) by the LoW. Two approaches were used to assess the five calculation methods. The first approach assessed therelative ranking of the five calculation methods by the frequency of their classification of waste streams as H. The relative ranking of the five methods (from most severe to less severe) is: Method 3 > Method 1 > Method 2 with extended M -factors > Method 2 > Method 4. This reflects the arithmetic ranking of the concentration limits of each method when assuming M  = 10, and is independent of the waste streams, or the H/NH/Mirror status of the waste streams. A second approach is theabsolute matching or concordance with the LoW. The LoW is taken as a reference method and the H wastes are all supposed to be HP 14. This point is discussed in the paper. The concordance for one calculation method is established by the number of wastes with identical classification by the considered calculation method and the LoW (i.e. H to H, NH to NH). The discordance is established as well, that is when the waste is classified "H" in the LoW and "NH" by calculation (i.e. an under-estimation of the hazard). For Data Set #1, Method 2 with extended M -factors matches best with the LoW (80% concordant H and non-H by LoW, and 13% discordant for H waste by LoW). This method more correctly classifies wastes containing substances with high ecotoxicity. Methods 1 and 3 have nearly as good matches (76% and 72% concordant H and non-H by LoW, and 13% and 6% respectively discordant for H waste by LoW). Method 2 with extended M -factors, but limited to the M -factors published in the CLP has insufficient concordance (64% concordant H and non-H by LoW, and 50% discordant for H waste by LoW). As the same method with extended M -factors gives the best performance, the lower performance is due to the limited set of M -factors in the CLP. Method 4 is divergent (60% concordant H and non-H by LoW, and 56% discordant for H waste by LoW). For Data Set #2, Methods 2 and 4 do not correctly classify 24 air pollution control residues from incineration 19 01 07 ∗ (3/24 and 2/24 respectively), and should not be used, while Methods 3, 1 and 2 with extended M -factors successfully classify 100% of them as hazardous. From the two sets of data, Method 2 with extended M -factors (corresponding more closely to the CLP methods used for products) matches best with the LoW when the LoW code is safely known, and Method 3 and 1 will deviate from the LoW if the samples contain substances with high ecotoxicity (in particular PAHs). Methods 2 and 4 are not recommended. Formally, this conclusion depends on the waste streams that are used for the comparison of methods and the relevancy of the classification as hazardous for ecotoxicity in the LoW. Since the set is large (120 waste streams) and no selection has been made here in the available data, the conclusion should be robust.